Plasma concentrations of fenbendazole (FBZ) and oxfendazole in alpacas (Lama pacos) after single intravenous and oral dosing of FBZ - Lakritz J (Dove Medical Press, 2015)
Jeffrey Lakritz,1 Daniel Linden,2 David E Anderson,3 Terri A Specht4 1Department of Veterinary Clinical Sciences, College of Veterinary Medicine, The Ohio State University, Columbus, OH, USA; 2Department of Agriculture and Engineering Technologies, College of Food, Agriculture and Environmental Sciences, The Ohio State University, Wooster, OH, USA; 3Department of Large Animal Clinical Sciences, College of Veterinary Medicine, University of Tennessee, Knoxville, TN, USA; 4Four Star Veterinary Service, Chickasaw, OH, USA Abstract: The objective of this study was to determine plasma pharmacokinetics and bioavailability of fenbendazole (FBZ) and oxfendazole (OFZ) after intravenous (iv) and oral administrations of FBZ (5 mg/kg) to alpacas. Plasma concentrations of FBZ and OFZ after administration of FBZ iv and orally (5 mg/kg) were determined by high-performance liquid chromatography with ultraviolet detection. Total clearance (CL) of FBZ was 16.5±4 mL/kg/min (range: 4–31 mL/kg/min), and steady-state volume of distribution (Vdss) was 3.3±1 L/kg (range: 1.7–7.4 L/kg). The terminal phase half-life of FBZ after iv administration was 5.9±3.8 hours (range: 0.8–20 hours). After oral administration, the FBZ terminal phase half-life was 23±5 hours (range: 9–37 hours) and the systemic bioavailability of FBZ was 16%±6% (range: 1%–41%). Peak FBZ concentrations after oral administration were 0.13±0.05 µg/mL (range: 0.05–0.28 µg/mL) at 10 hours (range: 8–12 hours). Peak plasma OFZ concentrations after oral dosing with FBZ (5 mg/kg) were 0.14±0.05 µg/mL (0.05–0.3 µg/mL) at 24±7 hours (range: 12–48 hours). FBZ clearance is lower in comparison to that of other species. Systemic availability of FBZ after oral administration is low after oral dosing. Metabolites of FBZ produced by alpacas are similar to those observed in other species. Keywords: bioavailability, benzimidazoles, camelid, pharmacokinetics